INTERAKSI BAHASA DAN IDENTITAS BUDAYA DALAM TRADISI PASAR KAMIS WAGE DESA PENGGARIT KABUPATEN PEMALANG: KAJIAN SOSIOLINGUISTIK PRAKTIS - Haryanto; Ika Septiana (STKIP Subang, 2026)
The Kamis Wage Market tradition in Penggarit Village, Pemalang Regency, is a form of local cultural preservation that still survives amid modernization. This study aims to describe language interaction, language variation, and the social function of language in buying and selling activities at Kamis Wage Market. This study used a qualitative descriptive method with an interactional sociolinguistic approach. Data were obtained through observation, documentation, interviews, and merchant-buyer conversation transcripts. Data analysis was conducted using Dell Hymes’ ethnography of communication theory and Chaer and Agustina’s language variation theory. The results show that Javanese krama and ngoko dominate social interactions in the market. In addition, code-switching and code-mixing phenomena between Javanese and Indonesian were found. Local terms such as klitik function as symbols of Penggarit community cultural identity. Language functions not only as a communication tool but also as a means of cultural preservation, social solidarity, and local identity formation. The Kamis Wage Market tradition demonstrates that language practices play an important role in maintaining local culture amid globalization.